Problematic Firms Mostly Take More Risks? : Prospect Theory Testing in Indonesia - Rahman, Fernanda Alfian; Yulianto, Arief (Universitas Negeri Semarang, 2021)
Prospect Theory Kahneman & Tversky (1979) is a behavioral theory that discusses risk taking viewed under certain conditions, whether in a win or loss condition. There is inconsistent behavior between theory and reality in companies in Indonesia. This research method uses a quantitative approach with the object of research being all companies listed on the Indonesia Stock Exchange from 2010 to 2019. The sample selection uses a purposive sampling method. The sample used as many as 206 companies with 1614 observations. This research uses ANOVA data analysis technique. Based on the results of this study, it shows that prospect theory is not supported in this study